Adaptation and Validation of Psychological Capital Questionnaire (PCQ-12) in Academic Context: Rasch Model Analysis - Istiqomah Istiqomah; Bambang Budi Wiyono; Hetti Rahmawati; Tutut Chusniyah; Azidah Abu Ziden (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Psychological capital is the condition of persons maintaining a positive attitude and effectively facing unpleasant conditions. This enables the completion of assignments and preparation for future success. Adaptation of psychological capital questionnaire for Indonesia was due to the absence of a measuring tool used within educational context. Therefore, this study aimed to adapt and validate Psychological Capital Questionnaire (PCQ-12) in the Indonesian language. The subjects comprised Senior high school (SMA) students from the Malang Raya area, totaling 348 participants. Furthermore, data analysis was conducted using Rasch model. The results showed that the PCQ-12 met the principles of unidimensionality and local independence. The Questionnaire comprised 12 items, with an instrument, item, and person reliability of 0.89, 0.98, and 0.88, respectively. Items that were challenging to agree upon included numbers 2, 5, 7, and 11, as well as items 8, 9, and 12. The PCQ-12 appropriately categorized response options into 6 choices, ensuring its suitability for use in Indonesia.